Management of Severe Scoliosis with Pulmonary Arterial Hypertension: A Single-Center Retrospective Case Series Study. (8th February 2022) - Li, Qiang; Zeng, Fei; Chen, Tao; Liang, Mengqiu; Lei, Xue; Liang, Yijian; Zheng, Chuandong; Huang, He
Aims: To determine the impact of anesthesia encountered and to optimize the treatment of perioperative pulmonary arterial hypertension (PAH) in an effort to improve perioperative management and reduce complications. Methods: We conducted a retrospective analysis of scoliosis patients with PAH who underwent scoliosis surgery. Results: During this period, we identified a total of 22 patients. Their mean age was 22.18 ± 2.11 years. 16 PAH patients (72.72%) received PAH-specific treatment. Only Propofol-based TIVA was used intraoperatively. During the procedure, pulmonary artery catheters and PICCO catheters were placed in all patients to monitor intraoperative and postoperative mPAP, MAP, PRVI and SRVI. During tracheal intubation and intraoperative awake testing, mPAP generally tended to increase in all patients. 6 patients (27.27%) received intraoperative PAH-Specific therapy. All patients received oral sildenafil (75-100 mg/d orally), and 9 patients received postoperative oral sildenafil combined with nebulized iloprost (20 μg/d); intravenous treprostinil (2 ng/kg/min started and titrated to 10-17.5 ng/kg/min); or bosentan (250 mg/d) postoperatively. 7 patients (31.82%) reported postoperative complications, including 2 cases of respiratory failure requiring reintubation, 1 case of right heart failure, 2 cases of superficial surgical site infection, 1 case of fluid and electrolyte and acid-base imbalances, 2 cases of pneumonia and 1 case of pulmonary oedema with fluid overload. Two patients developed more than 1 postoperative complication. No in-hospital death occurred. Conclusions: The anesthetic management of scoliosis patients with PAH is important task that, like its own surgery, relies on the input of the multidisciplinary team for its success. Close monitoring, optimization of systemic blood pressure, pain control, oxygenation and ventilation, avoidance of exacerbating factors, and the use of vasopressors and pulmonary vasodilators when necessary are essential elements of management.